Answer:
![y=(1)/(2)(x-4)^2+13\text{ }\operatorname{\Rightarrow}(A)]()
Step-by-step explanation: We have to find the vertex form of the parabola equation from the given standard form of it:
![y=(1)/(2)x^2-4x+21\rightarrow(1)](https://img.qammunity.org/2023/formulas/mathematics/college/xac43579isweeb410g5ek5v48g3gthrrlc.png)
The general form of the vertex parabola equation is as follows:
![\begin{gathered} y=A(x-h)^2+k\rightarrow(2) \\ \\ \text{ Where:} \\ \\ (h,k)\rightarrow(x,y)\Rightarrow\text{ The Vertex} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/7cm9es6k7538wisj410u26gbqi7e1wfrj9.png)
Comparing the equation (2) with the original equation (1) by looking at the graph of (1) gives the following:
![(h,k)=(x,y)=(-4,13)](https://img.qammunity.org/2023/formulas/mathematics/college/vl5drcg3x10vagjd5t8vr0g8maoja7ngbu.png)
Therefore the vertex form of the equation is as follows:
![y=(1)/(2)(x-4)^2+13\Rightarrow(A)](https://img.qammunity.org/2023/formulas/mathematics/college/b97wiendb81z5yel367x46ajf6fx2sgxwc.png)
Therefore the answer is Option(A).